Safe Haskell | Safe-Inferred |
---|---|
Language | Haskell2010 |
Documentation
module Data.Functor
class Functor (f :: Type -> Type) where Source #
A type f
is a Functor if it provides a function fmap
which, given any types a
and b
lets you apply any function from (a -> b)
to turn an f a
into an f b
, preserving the
structure of f
. Furthermore f
needs to adhere to the following:
Note, that the second law follows from the free theorem of the type fmap
and
the first law, so you need only check that the former condition holds.
fmap :: (a -> b) -> f a -> f b Source #
Using ApplicativeDo
: '
' can be understood as
the fmap
f asdo
expression
do a <- as pure (f a)
with an inferred Functor
constraint.
Instances
Functor [] | Since: base-2.1 |
Functor Maybe | Since: base-2.1 |
Functor IO | Since: base-2.1 |
Functor Complex | Since: base-4.9.0.0 |
Functor Min | Since: base-4.9.0.0 |
Functor Max | Since: base-4.9.0.0 |
Functor First | Since: base-4.9.0.0 |
Functor Last | Since: base-4.9.0.0 |
Functor Option | Since: base-4.9.0.0 |
Functor Identity | Since: base-4.8.0.0 |
Functor Handler | Since: base-4.6.0.0 |
Functor STM | Since: base-4.3.0.0 |
Functor First | Since: base-4.8.0.0 |
Functor Last | Since: base-4.8.0.0 |
Functor Dual | Since: base-4.8.0.0 |
Functor Sum | Since: base-4.8.0.0 |
Functor Product | Since: base-4.8.0.0 |
Functor ReadPrec | Since: base-2.1 |
Functor ReadP | Since: base-2.1 |
Functor NonEmpty | Since: base-4.9.0.0 |
Functor P | Since: base-4.8.0.0 |
Functor (Either a) | Since: base-3.0 |
Functor ((,) a) | Since: base-2.1 |
Functor (Arg a) | Since: base-4.9.0.0 |
Functor (Proxy :: Type -> Type) | Since: base-4.7.0.0 |
Functor ((,,) a b) | Since: base-4.14.0.0 |
Functor (Const m :: Type -> Type) | Since: base-2.1 |
Functor f => Functor (Ap f) | Since: base-4.12.0.0 |
Functor f => Functor (Alt f) | Since: base-4.8.0.0 |
Functor ((->) r :: Type -> Type) | Since: base-2.1 |
Functor ((,,,) a b c) | Since: base-4.14.0.0 |
(Functor f, Functor g) => Functor (Product f g) | Since: base-4.9.0.0 |
(Functor f, Functor g) => Functor (Sum f g) | Since: base-4.9.0.0 |
(Functor f, Functor g) => Functor (Compose f g) | Since: base-4.9.0.0 |
($>) :: Functor f => f a -> b -> f b infixl 4 Source #
Flipped version of <$
.
Using ApplicativeDo
: 'as
' can be understood as the
$>
bdo
expression
do as pure b
with an inferred Functor
constraint.
Examples
Replace the contents of a
with a constant
Maybe
Int
String
:
>>>
Nothing $> "foo"
Nothing>>>
Just 90210 $> "foo"
Just "foo"
Replace the contents of an
with a constant Either
Int
Int
String
, resulting in an
:Either
Int
String
>>>
Left 8675309 $> "foo"
Left 8675309>>>
Right 8675309 $> "foo"
Right "foo"
Replace each element of a list with a constant String
:
>>>
[1,2,3] $> "foo"
["foo","foo","foo"]
Replace the second element of a pair with a constant String
:
>>>
(1,2) $> "foo"
(1,"foo")
Since: base-4.7.0.0
void :: Functor f => f a -> f () Source #
discards or ignores the result of evaluation, such
as the return value of an void
valueIO
action.
Using ApplicativeDo
: '
' can be understood as the
void
asdo
expression
do as pure ()
with an inferred Functor
constraint.
Examples
Replace the contents of a
with unit:Maybe
Int
>>>
void Nothing
Nothing>>>
void (Just 3)
Just ()
Replace the contents of an
with unit, resulting in an Either
Int
Int
:Either
Int
()
>>>
void (Left 8675309)
Left 8675309>>>
void (Right 8675309)
Right ()
Replace every element of a list with unit:
>>>
void [1,2,3]
[(),(),()]
Replace the second element of a pair with unit:
>>>
void (1,2)
(1,())
Discard the result of an IO
action:
>>>
mapM print [1,2]
1 2 [(),()]>>>
void $ mapM print [1,2]
1 2